Microeconomics theory and applications - Maddala, G. S. (McGraw-Hill, 1989)
"Microeconomics" provides a contemporary, comprehensive and clear coverage of intermediate microeconomics within a European context. The text aims to ensure effective understanding of the essential principles and is as a result unique in its patient and careful coverage of the core microeconomics topics, (including, for example, the analysis of consumer demand, the cost of production and the pricing of products under different forms of industrial organization). "Microeconomics" brings theory to life with its many pan-European examples and extended applications. The extended applications include VAT on domestic energy, energy conservation, land use restrictions in European agriculture, monopsony, and minimum wages laws. Highlighted examples include retirement pensions, pricing strategy at Euro-Disney, and health care costs across Europe.